In vitro and in vivo Evaluation of Triptolide-loaded Pluronic P105 Polymeric Micelles - Li, H.; Wen, X.-S.; Di, W. (Arzneimittelforschung, 2012)
Thin film method was applied successfully to prepare Triptolide (TP)-loaded micelles system. With a dynamic light scattering sizer and a transmission electron microscopy, it was shown that the TP-loaded micelles had a mean size of 84.3±6.4 nm with a spherical shape. The in vitro release profiles indicated that the release of TP from the micelles exhibited a sustained release behavior. A similar phenomenon was also observed in a pharmacokinetic study in rats, in which AUC of the micelles formulation were 4.7-fold higher than that of TP injection. The biodistribution study in rats showed that the TP-loaded micelles not only decreased drug uptake by liver, but also increased distribution of drug in ovary. The present work demonstrated the feasibility of controlled delivery of TP utilizing micelles system.
Keywords: TP-loaded micelles; in vitro release; pharmacokinetic study; biodistribution study